DINAMIKA HUKUM DAN HAK ASASI MANUSIA DI NEGARA-NEGARA MUSLIM - Hafiz, Muhammad (Al-Ahkam, 2013)
Muslim countries often stuck in a dilemmatic situation between be exclusively with retaining the Islamic principles of human rights through Islamic law or follow the principles of human rights which is regulated internationally through Universal Declaration of Human Rights (UDHR). The existence of Independent Permanent Commission of Human Rights (IPHRC) as one of the core institutions of organization of the Islamic Cooperation (OIC) intended to be a mediator for the occurrence of constructive dialogue between human rights discourse on one side with Islamic law on the other side. This is the way to reduce dichotomous view that impact on gaps and conflict. The equivalent dialogue continuously between two entities, Islamic law and human rights must always be attempts to open opportunities in more widely shared understanding and in turn will facilitate the achievement of progress and the protection of human rights in Muslim countries. This dialogue also important to remove the negative stigma against Islamic law that is often accused of violating human rights. and also to open space of interpretation to Islamic law that relevance with contemporary life.